Hunting dinosaurs - Psihoyos, Louie; Knoebber, John. (New York : Random House, 1994)
Text, photographs, and illustrations document the work of present-day scientists who search for dinosaur fossils throughout the world.
Includes bibliographical references and index.
Notable/Best Books (A.L.A.).
Wilson's Public Library.
Wilson's Senior High School.
Adult
Keywords: Fossils; Paleontology; Dinosaurs; Fossils